Standardized Reporting of Experimental Iron Smelting - A modest (?) Proposal - Darrell Markewitz (EXARC Journal)
The development of effective bloomery iron smelting has progressed over the past decades from the first repeated experiments into documented, effective, methods. This progression has primarily been the work of often isolated individuals, many with great practical experience as artisans, but most often with little formal academic training. The overall result is a patchwork of recording methods and descriptions, with greatly differing degrees of detail. Experience contrasts experiment, with many different approaches, and often objectives, as the goals. The author, drawing on almost 20 years of experience with bloomery iron smelting, and a foot in both the artisan and academic worlds, suggests some standard measurements and record keeping methods, presented in the hope of making the sharing of information easier. As this article is also intended for first time experimenters, and both artisan and academic experimenters, indulgence from well experienced iron makers is requested over many detailed explanations, and the level of detail presented. It is well understood that those experimenters working within an ongoing series may not record all the suggested details every time.